From privacy impact assessment to Social Impact Assessment - Edwards, Lilian; McAuley, Derek; Diver, Laurence (2016)
In order to address the continued decline in consumer trust in all things digital, and specifically the Internet of Things (IoT), we propose a radical overhaul of IoT design processes. Privacy by Design has been proposed as a suitable framework, but we argue the current approach has two failings: it presents too abstract a framework to inform design; and it is often applied after many critical design decisions have been made in defining the business opportunity. To rebuild trust we need the philosophy of Privacy by Design to be transformed into a wider Social Impact Assessment and delivered with practical guidance to be applied at product/service concept stage as well as throughout the system’s engineering.